Exploring the monogamy principle in the Samin community’s customary marriages in Kudus: Harmonisation of tradition and state law - Iman, Iman Fadhilah; Tedi Kholiludin; Muhammad Lutfi Hakim; Ubbadul Adzkiya’ (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2024)
This article explores the practice of monogamy in customary marriage within the Samin community in Larikrejo Village, Kudus, rooted in the principle of “bojo siji kangge saklawase”. The uniqueness of this customary marriage practice is evident in the reflection of the values of Samin society, passed down through generations by their ancestors. Its significance becomes more pronounced considering the prevalence of polygamous practices in customary marriages across various regions of Indonesia. Despite the allowance of polygamy within certain limits by state law, the Samin community chooses to uphold their customary marriage traditions. This article presents the findings of field research involving four key informants and direct observations of customary marriage practices as the primary source. The research reveals that the practice of monogamy within Samin community marriages reflects the embodiment of the “bojo siji kangge saklawase” principle, manifested through a solemn pledge to one wife made by prospective grooms during the paseksen stage, the final step in the customary marriage ceremony following nyumuk (betrothal) and pasuwitan (marriage contract). The obligation to make this pledge aims to prevent potential conflicts within Samin families. This monogamous practice aligns with the principles of monogamy and the objectives of marriage in state law, creating harmony and stability within the family institution. This study provides in-depth insights into the unique relationship between local values and state regulations amidst the challenges of modernization and ongoing social changes.